2015
DOI: 10.1097/cji.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Derived From Human Melanoma Draining Lymph Nodes Mediate Melanoma-specific Antitumor Responses In Vitro and In Vivo in Human Melanoma Xenograft Model

Abstract: It has been established in murine models that lymph nodes draining a progressively growing tumor contain antigen-specific T cells capable of mediating protective immune responses upon adoptive transfer. However, naturally occurring human tumor-draining lymph nodes (TDLNs) have yet to be fully investigated. In this study, we analyzed TDLNs from patients with stage III melanoma who were undergoing routine lymph node dissection. Following short-term (14 d) culture activation with anti-CD3/anti-CD28 microbeads and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…Our results have demonstrated that the MDLN samples contain antigen specific CD4 + and CD8 + T cells that could mediate melanoma cell apoptosis in vitro and improve mice survival in vivo (7, 8). MDLN is secondary lymphoid organ where both CD4 + and CD8 + T cells experience melanoma antigens in vivo in the presence of APCs, i.e., dendritic cells (DCs) and relevant cytokines (9).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Our results have demonstrated that the MDLN samples contain antigen specific CD4 + and CD8 + T cells that could mediate melanoma cell apoptosis in vitro and improve mice survival in vivo (7, 8). MDLN is secondary lymphoid organ where both CD4 + and CD8 + T cells experience melanoma antigens in vivo in the presence of APCs, i.e., dendritic cells (DCs) and relevant cytokines (9).…”
Section: Introductionmentioning
confidence: 78%
“…Cells were washed twice with CM and counted using a cytometer and Trypan-blue exclusion to determine yield and viability. T cell activation and expansion were performed according to our previous publication (7, 8). Briefly, freshly harvested MDLN cells were incubated overnight with CM containing 30 I.U.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations